1990
DOI: 10.1080/03014469000000952
|View full text |Cite
|
Sign up to set email alerts
|

The cyclical nature of prepubertal growth

Abstract: We have examined the complete longitudinal height velocity (HV) data of 135 (80 male and 55 female) chromosomally normal children from the Edinburgh Longitudinal Growth Study who were measured six-monthly between age 3 years and the onset of the adolescent growth spurt. Individual HV curves appeared to consist of a regular series of accelerations and decelerations in a cyclical fashion. After excluding variations due to measurement error, and basing the analysis on the pattern of acceleration, we were able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
5

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 25 publications
4
52
0
5
Order By: Relevance
“…This could be due to factors like genetics, nutrition and obesity. A recent systematic review found that excess body weight in infancy advances several pubertal indicators including age at menarche (31). The present analyses corroborates this finding at the hormonal level, as we found that top weight gainers (and overweight) girls initiated hormonal (by LH) puberty 10.8 mo earlier than normal weight gain girls.…”
Section: Ages At Hormonal Onset Of Puberty and Body Compositionsupporting
confidence: 81%
“…This could be due to factors like genetics, nutrition and obesity. A recent systematic review found that excess body weight in infancy advances several pubertal indicators including age at menarche (31). The present analyses corroborates this finding at the hormonal level, as we found that top weight gainers (and overweight) girls initiated hormonal (by LH) puberty 10.8 mo earlier than normal weight gain girls.…”
Section: Ages At Hormonal Onset Of Puberty and Body Compositionsupporting
confidence: 81%
“…Successive measurements of growth velocity are not well correlated because of the cyclical nature of growth over the short (1-yr) and longer term (2-yrs) [25,26]. Given the cyclical nature of growth, control data are essential for any study and, because of the longer-term trends in childhood growth ( fig.…”
Section: Growth During Childhoodmentioning
confidence: 99%
“…The greatest annual growth in sitting height in a Taiwanese population [3] was 61 mm (in boys) and 63 mm (in girls) at age 8.5 years, with a second peak of 46 mm in boys (at age 12.5 years) and 32 mm in girls (at age 11.5 years). Sitting height increases are not necessarily synchronized with leg growth [4,5]. Howell et al [6] reported continued growth (about 14 mm increase in sitting height) after skeletal maturity, indicating that the spine continues to grow after cessation of limb growth.…”
Section: Introductionmentioning
confidence: 99%